Method for producing magnesia carbon brick from low-carbon reduced magnesia
By preparing a functional enhancer of nano-titanium dioxide loaded on porous microspheres, the problem of decreased strength and thermal shock resistance of low-carbon magnesia-carbon bricks was solved, and the high strength and oxidation resistance of magnesia-carbon bricks were improved, thus extending their service life.
Patent Information
- Application Number
- CN202511323855.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-09-17
AI Technical Summary
Existing low-carbon magnesia-carbon bricks exhibit a significant decrease in strength and thermal shock resistance after reducing carbon content, making it difficult to form an effective multi-level reinforcement structure and self-healing mechanism using existing additives.
Porous microspheres were prepared using boron carbide, aluminum powder, calcium powder, and a compound pore-forming agent. Nano-titanium dioxide was loaded onto these microspheres, and micron-sized grooves were formed by plasma etching. A functional enhancer was then prepared to enhance the interfacial bonding and self-healing ability of magnesia-carbon bricks.
It improves the mechanical properties and thermal shock resistance of magnesia-carbon bricks, extends their service life, and enhances their oxidation resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, in particular to a method for producing magnesia-carbon bricks by reducing low-carbon magnesia. Background Art
[0002] Magnesia carbon bricks, due to their excellent high-temperature resistance and resistance to slag erosion, are widely used in the lining of metallurgical equipment such as converters, electric furnaces, and ladles. Traditional magnesia carbon bricks typically contain 8-20% pyrocarbon. While this high carbon content improves slag resistance and thermal shock stability, it also leads to problems such as excessive thermal conductivity, susceptibility to oxidation, increased energy consumption, and carbon enrichment with molten steel during use. With the development of clean steelmaking technology, the demand for low-carbon magnesia carbon bricks is becoming increasingly urgent.
[0003] However, reducing the carbon content significantly reduces the strength and thermal shock resistance of magnesia-carbon bricks. To address this issue, existing technologies often use the addition of metal powders (such as Al, Si, Mg), carbides (such as SiC, B4C), borides, etc. as antioxidants and reinforcing phases. These react at high temperatures to form a ceramic binder phase or promote magnesium vapor circulation to compensate for the performance loss caused by the reduced carbon content. However, these additives often have a single function, limited improvement effects, and it is difficult to form an effective multi-level reinforcement structure and self-repair mechanism within the material. Based on this, the present invention provides a method for producing magnesia-carbon bricks by reducing low-carbon magnesia sand to address the technical problems mentioned above. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for producing magnesia carbon bricks by reducing low-carbon magnesia sand. The produced magnesia carbon bricks not only have excellent mechanical properties, but also have outstanding thermal shock stability and antioxidant properties, which effectively ensures the quality and quality of the produced magnesia carbon bricks while also extending their service life to a certain extent.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for producing magnesia-carbon bricks by reducing low-carbon magnesia comprises the following steps: Step 1: Weigh 80-90 parts of magnesia, 3-5 parts of functional enhancer, 1-3 parts of aluminum powder, 0.3-1 parts of aluminum nitride, 2-3 parts of carbon black, 3-5 parts of flake graphite and 3-5 parts of phenolic resin respectively by weight for later use; The magnesium oxide content in the magnesia is ≥97%, and the particle size composition of the magnesia is as follows: 3-5 mm magnesia accounts for 20-25%, 1-3 mm magnesia accounts for 23-26%, 0.074-1 mm magnesia accounts for 20-25%, and the balance is fine magnesia ≤0.074 mm; Step 2: Mix the magnesia except fine magnesia with phenolic resin, add the remaining raw materials except fine magnesia after mixing, add fine magnesia at a low speed, and then mix at a high speed to obtain a mixed slurry; inject the mixed slurry into the prepared mold, and press and heat treat in sequence to obtain magnesia-carbon bricks.
[0006] Furthermore, the low-speed stirring speed is 50-80 r / min, and the stirring time is 3-5 min; the high-speed stirring speed is 100-150 r / min, and the stirring time is 30-60 min.
[0007] Furthermore, the heat treatment temperature is 180-220° C., and the heat treatment time is 15-20 hours; and a 1000T electric screw brick press is used for pressing and molding.
[0008] Furthermore, the preparation method of the functional enhancer is: In the first step, 30% of the total amount of boron carbide, aluminum powder, and calcium powder are placed in a ball mill. After ball milling at a rate of 250-350 r / min under argon protection for 2-3 hours, the composite pore-forming agent and the remaining boron carbide powder are added and ball milling is continued under argon protection for 3-4 hours. The resulting mixed powder is then spray granulated to obtain composite microspheres with a particle size of 30-50 μm. The obtained microspheres are sintered at a high temperature under argon protection and then naturally cooled to room temperature to obtain porous microspheres. The mass ratio of boron carbide, aluminum powder, calcium powder, and composite pore-forming agent is 65-80:10-25:5-15:25-35. The second step is to adjust the pH of a 0.05-0.15 mol / L tetrabutyl titanate ethanol solution to 3.3-3.8 with dilute nitric acid, add the porous microspheres at a ratio of 30-60 g / L, and after ultrasonic dispersion, heat the resulting mixture at 180-200°C for 6-10 hours. After the reaction is completed, the reaction product is filtered, washed, and sintered at high temperature to obtain modified porous microspheres. The third step is to place the modified porous microspheres in a plasma treatment chamber, introduce a mixed gas of argon and oxygen, and plasma etch the modified porous microspheres for 30-40 minutes at a pressure of 45-60 Pa; after etching, the functional enhancer is obtained.
[0009] Furthermore, the compound pore-forming agent is compounded by starch and polymethyl methacrylate in a mass ratio of 2-4:1.
[0010] Furthermore, during spray granulation, the inlet temperature is 220-260° C., the outlet temperature is 90-110° C., and the atomization pressure is 0.4-0.6 MPa.
[0011] Furthermore, the specific operation of high-temperature sintering in the first step is as follows: under argon protection, the temperature in the sintering equipment is increased to 1100-1300°C at a rate of 5-10°C / min, and the heat treatment is carried out at this temperature for 2-3 hours.
[0012] Furthermore, during plasma etching, the flow ratio of argon to oxygen is 3-5:1, and the power during etching is set to 250-400W.
[0013] Furthermore, in the second step, the frequency of ultrasonic dispersion is 25-35 kHz, and the ultrasonic dispersion time is 20-30 min.
[0014] Furthermore, the high-temperature sintering in the second step is carried out in a nitrogen atmosphere, and the temperature of the high-temperature sintering is 450-550° C., and the time of the high-temperature sintering is 2-3 hours.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses boron carbide powder, aluminum powder, calcium powder and compound pore-forming agent as raw materials to prepare porous microspheres with a pore size of 0.5-1μm, and uses porous microspheres as the core skeleton. The surface of the porous microspheres and their porous structure are loaded with spike-shaped nano-titanium dioxide with catalytic activity in a high temperature environment by a sol-gel method to prepare modified porous microspheres. Spiky nano-titanium dioxide can promote carbon gasification reaction and carbon thermal reduction reaction of magnesia in a high temperature environment, continuously generating magnesium vapor, which reacts with slag or re-oxidizes and deposits at the erosion interface of magnesia-carbon bricks, dynamically blocking pores and cracks, forming a dense healing layer, thereby giving magnesia-carbon bricks excellent self-repairing ability and resistance to slag penetration and erosion. Finally, the surface of the functional enhancer treated with plasma etching forms rich micron grooves with high roughness and activity, which not only improves its dispersibility in magnesia-carbon bricks, but also strengthens the interface bonding with magnesia and binder, ensuring effective stress transmission and efficient function of functional components.
[0016] The functional enhancer prepared by the present invention can be used as a reinforcing phase of magnesium carbon bricks. Its multi-level structure significantly improves the interfacial bonding strength of the composite material through a mechanical interlocking effect. The nano-spikes provide point contact anchoring, the micron grooves achieve surface contact interlocking, and the internal pores promote the matrix pinning effect. At the same time, boron carbide reacts chemically with aluminum powder and calcium powder under high temperature conditions to generate a composite glass-ceramic protective film with high melting point, low volatility calcium borate as the skeleton and aluminum borate as the reinforcing phase. The protective film is extremely stable and dense at ultra-high temperatures, and can more durably and effectively cover the graphite surface, isolating oxygen penetration and slag erosion, thereby significantly delaying the oxidation loss of the core carbon binding phase. The spike-shaped nano-titanium dioxide structure helps to improve the high-temperature stability and potential catalytic purification capabilities of magnesium carbon bricks.
[0017] In summary, the magnesia carbon bricks produced with functional enhancers as raw materials not only have excellent mechanical properties, but also have outstanding thermal shock stability and antioxidant properties, which effectively ensures the quality of the produced magnesia carbon bricks while also extending their service life to a certain extent. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0019] Example 1 A method for producing magnesia-carbon bricks by reducing low-carbon magnesia comprises the following steps: Step 1: Weigh 80 parts of magnesia, 3 parts of functional enhancer, 1 part of aluminum powder (average particle size of 350 mesh), 0.3 parts of aluminum nitride (average particle size of 80 nm), 2 parts of carbon black (average particle size of 150 nm), 3 parts of flake graphite (average particle size of 0.12 mm), and 3 parts of phenolic resin (viscosity of 10,000 cp at 25°C) respectively, and set aside; The magnesium oxide content in the magnesia is ≥ 97%, and the particle size composition of the magnesia is as follows: 3 mm magnesia accounts for 20%, 1 mm magnesia accounts for 23%, 0.074 mm magnesia accounts for 25%, and the balance is fine magnesia ≤ 0.074 mm; Step 2: Mix the magnesia except fine magnesia with phenolic resin, add the remaining raw materials except fine magnesia after mixing, add fine magnesia at a low speed, and then mix at a high speed to obtain a mixed slurry; inject the mixed slurry into the prepared mold, and press and heat treat in sequence to obtain magnesia carbon bricks; Among them, the low-speed stirring speed is 50r / min, and the stirring time is 5min; the high-speed stirring speed is 100r / min, and the stirring time is 60min; The heat treatment temperature is 180° C., and the heat treatment time is 20 h. A 1000T electric screw brick press is used for pressing and molding.
[0020] The preparation method of the functional enhancer is: In the first step, 30% of the total amount of boron carbide, aluminum powder, and calcium powder were placed in a ball mill. After ball milling at a rate of 250 r / min under the protection of argon for 3 hours, the composite pore-forming agent and the remaining boron carbide powder were added and ball milling was continued under the protection of argon for 3 hours. The resulting mixed powder was then spray granulated to obtain composite microspheres with a particle size of 30 μm. The obtained microspheres were sintered at high temperature under the protection of argon and then naturally cooled to room temperature to obtain porous microspheres. The mass ratio of boron carbide, aluminum powder, calcium powder, and composite pore-forming agent was 65:10:5:25. The compound pore-forming agent is prepared by compounding starch and polymethyl methacrylate in a mass ratio of 2:1; During spray granulation, the inlet temperature is 220°C, the outlet temperature is 90°C, and the atomization pressure is 0.4 MPa; The specific operation of high-temperature sintering in the first step is as follows: under argon protection, the temperature in the sintering equipment is raised to 1100°C at a rate of 5°C / min, and the temperature is kept at this temperature for 3 hours; The second step is to adjust the pH of a 0.05 mol / L ethanol solution of tetrabutyl titanate to 3.3 with dilute nitric acid, add the porous microspheres at a ratio of 30 g / L, and after ultrasonic dispersion, incubate the resulting mixture at 180°C for 10 hours. After the reaction is complete, filter, wash, and sinter the reaction product at high temperature to obtain modified porous microspheres. The ultrasonic dispersion frequency is 25 kHz, and the ultrasonic dispersion time is 30 min. The high-temperature sintering is carried out in a nitrogen atmosphere, and the high-temperature sintering temperature is 450° C., and the high-temperature sintering time is 3 h. The third step is to place the modified porous microspheres in a plasma treatment chamber, introduce a mixed gas of argon and oxygen, and plasma etch the modified porous microspheres for 40 minutes at 45 Pa; after etching, the functional enhancer is obtained.
[0021] Example 2 The production method of a magnesia carbon brick provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the produced magnesia carbon brick and the preparation method of the function enhancer are not exactly the same. The specific composition of the magnesia carbon brick and the preparation method of the function enhancer in this embodiment are as follows: The magnesia carbon brick is made of the following raw materials in parts by weight: 85 parts of magnesia, 4 parts of functional enhancer, 2 parts of aluminum powder, 0.5 parts of aluminum nitride, 2.5 parts of carbon black, 4 parts of flake graphite and 4 parts of phenolic resin.
[0022] The preparation method of the functional enhancer is: In the first step, 30% of the total amount of boron carbide, aluminum powder, and calcium powder were added to a ball mill. After ball milling at 300 r / min under argon protection for 3 hours, the composite pore-forming agent and the remaining boron carbide powder were added and ball milling was continued under argon protection for 4 hours. The resulting mixed powder was then spray granulated to obtain composite microspheres with a particle size of 40 μm. The obtained microspheres were sintered at high temperature under argon protection and then naturally cooled to room temperature to obtain porous microspheres. The mass ratio of boron carbide, aluminum powder, calcium powder, and composite pore-forming agent was 70:20:10:30. The compound pore-forming agent is prepared by compounding starch and polymethyl methacrylate in a mass ratio of 3:1; During spray granulation, the inlet temperature is 240°C, the outlet temperature is 100°C, and the atomization pressure is 0.5 MPa; The specific operation of high-temperature sintering in the first step is as follows: under argon protection, the temperature in the sintering equipment is raised to 1200°C at a rate of 10°C / min, and the temperature is kept at this temperature for 3 hours; In the second step, the pH of a 0.1 mol / L ethanol solution of tetrabutyl titanate was adjusted to 3.5 with dilute nitric acid, and the porous microspheres were added at a ratio of 40 g / L. After ultrasonic dispersion, the resulting mixture was kept at 190°C for 8 hours. After the reaction was completed, the reaction product was filtered, washed, and sintered at high temperature to obtain modified porous microspheres. The ultrasonic dispersion frequency is 30 kHz, and the ultrasonic dispersion time is 25 min. The high-temperature sintering is carried out in a nitrogen atmosphere, and the high-temperature sintering temperature is 500° C., and the high-temperature sintering time is 3 h. The third step is to place the modified porous microspheres in a plasma treatment chamber, introduce a mixed gas of argon and oxygen, and plasma etch the modified porous microspheres for 35 minutes at 50 Pa; after etching, the functional enhancer is obtained. Example 3 The production method of a magnesia carbon brick provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the produced magnesia carbon brick and the preparation method of the function enhancer are not exactly the same. The specific composition of the magnesia carbon brick and the preparation method of the function enhancer in this embodiment are as follows: The magnesia carbon brick is made of the following raw materials in parts by weight: 90 parts of magnesia sand, 5 parts of functional enhancer, 3 parts of aluminum powder, 1 part of aluminum nitride, 3 parts of carbon black, 5 parts of flake graphite and 5 parts of phenolic resin.
[0023] The preparation method of the functional enhancer is: In the first step, 30% of the total amount of boron carbide, aluminum powder, and calcium powder were placed in a ball mill. After ball milling at a rate of 350 r / min under the protection of argon for 2 hours, the composite pore-forming agent and the remaining boron carbide powder were added and ball milling was continued under the protection of argon for 4 hours. The resulting mixed powder was then spray granulated to obtain composite microspheres with a particle size of 50 μm. The obtained microspheres were sintered at high temperature under the protection of argon and then naturally cooled to room temperature to obtain porous microspheres. The mass ratio of boron carbide, aluminum powder, calcium powder, and composite pore-forming agent was 80:25:15:35. The compound pore-forming agent is prepared by compounding starch and polymethyl methacrylate in a mass ratio of 4:1; During spray granulation, the inlet temperature is 260°C, the outlet temperature is 90°C, and the atomization pressure is 0.6MPa; The specific operation of high-temperature sintering in the first step is as follows: under argon protection, the temperature in the sintering equipment is raised to 1300°C at a rate of 10°C / min, and the temperature is kept at this temperature for 2 hours; In the second step, the pH of a 0.15 mol / L ethanol solution of tetrabutyl titanate was adjusted to 3.8 with dilute nitric acid, and the porous microspheres were added at a ratio of 60 g / L. After ultrasonic dispersion, the resulting mixture was kept at 200°C for 6 hours. After the reaction was completed, the reaction product was filtered, washed, and sintered at high temperature to obtain modified porous microspheres. The ultrasonic dispersion frequency is 35 kHz, and the ultrasonic dispersion time is 20 min. The high-temperature sintering is carried out in a nitrogen atmosphere, and the high-temperature sintering temperature is 550° C., and the high-temperature sintering time is 2 h. The third step is to place the modified porous microspheres in a plasma treatment chamber, introduce a mixed gas of argon and oxygen, and plasma etch the modified porous microspheres for 30 minutes at 60 Pa; after etching, the functional enhancer is obtained.
[0024] The difference between the comparative example and Example 1 is that an equal amount of boron carbide is used to replace the functional enhancer in this comparative example. Performance test: The relevant performance of the magnesia carbon brick samples (with a size of 300 mm × 150 mm × 150 mm) provided in Examples 1-3 and the comparative example were tested, and the test data obtained were recorded in the following table:
[0025] Note: The specific steps of the seismic performance test are: heat treatment at 1100℃ followed by rapid air cooling, followed by application of 0.3MPa pressure. If the sample is not damaged, the next thermal shock test is carried out. The thermal shock resistance is characterized by the number of thermal shocks.
[0026] Comparing and analyzing the relevant data in the table shows that the magnesia-carbon bricks produced by the present invention not only have excellent mechanical properties, but also have outstanding thermal shock stability and oxidation resistance. This effectively ensures the quality of the magnesia-carbon bricks produced while also extending their service life to a certain extent. This shows that the method for producing magnesia-carbon bricks from low-carbon reduced magnesia provided by the present invention has a broader market prospect and is more suitable for promotion.
[0027] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0028] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for producing magnesia-carbon bricks by reducing low-carbon magnesia, characterized in that: The following steps are involved: Step 1: Weigh 80-90 parts of magnesia, 3-5 parts of functional enhancer, 1-3 parts of aluminum powder, 0.3-1 parts of aluminum nitride, 2-3 parts of carbon black, 3-5 parts of flake graphite and 3-5 parts of phenolic resin respectively by weight for later use; The magnesium oxide content in the magnesia is ≥97%, and the particle size composition of the magnesia is as follows: 3-5 mm magnesia accounts for 20-25%, 1-3 mm magnesia accounts for 23-26%, 0.074-1 mm magnesia accounts for 20-25%, and the balance is fine magnesia ≤0.074 mm; Step 2: Mix the magnesia except fine magnesia with phenolic resin, add the remaining raw materials except fine magnesia after mixing, add fine magnesia at a low speed, and then mix at a high speed to obtain a mixed slurry; inject the mixed slurry into the prepared mold, and press and heat treat in sequence to obtain magnesia-carbon bricks.
2. The method for producing magnesia-carbon bricks from low-carbon reduced magnesia according to claim 1, characterized in that: The low-speed stirring speed is 50-80r / min, and the stirring time is 3-5min; the high-speed stirring speed is 100-150r / min, and the stirring time is 30-60min.
3. The method for producing magnesia-carbon bricks from low-carbon reduced magnesia according to claim 1, characterized in that: The heat treatment temperature is 180-220°C, and the heat treatment time is 15-20h; a 1000T electric screw brick press is used for pressing and molding.
4. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 1, characterized in that: The preparation method of the functional enhancer is: In the first step, 30% of the total amount of boron carbide, aluminum powder, and calcium powder are placed in a ball mill. After ball milling at a rate of 250-350 r / min under argon protection for 2-3 hours, the composite pore-forming agent and the remaining boron carbide powder are added and ball milling is continued under argon protection for 3-4 hours. The resulting mixed powder is then spray granulated to obtain composite microspheres with a particle size of 30-50 μm. The obtained microspheres are sintered at a high temperature under argon protection and then naturally cooled to room temperature to obtain porous microspheres. The mass ratio of boron carbide, aluminum powder, calcium powder, and composite pore-forming agent is 65-80:10-25:5-15:25-35. The second step is to adjust the pH of a 0.05-0.15 mol / L tetrabutyl titanate ethanol solution to 3.3-3.8 with dilute nitric acid, add the porous microspheres at a ratio of 30-60 g / L, and after ultrasonic dispersion, heat the resulting mixture at 180-200°C for 6-10 hours. After the reaction is completed, the reaction product is filtered, washed, and sintered at high temperature to obtain modified porous microspheres. The third step is to place the modified porous microspheres in a plasma treatment chamber, introduce a mixed gas of argon and oxygen, and plasma etch the modified porous microspheres for 30-40 minutes at a pressure of 45-60 Pa; after etching, the functional enhancer is obtained.
5. The method for producing magnesia-carbon bricks from low-carbon reduced magnesia according to claim 4, characterized in that: The compound pore-forming agent is prepared by compounding starch and polymethyl methacrylate in a mass ratio of 2-4:
1.
6. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 4, characterized in that: During spray granulation, the inlet temperature is 220-260°C, the outlet temperature is 90-110°C, and the atomization pressure is 0.4-0.6MPa.
7. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 4, characterized in that: The specific operation of high temperature sintering in the first step is as follows: under argon protection, the temperature in the sintering equipment is raised to 1100-1300° C. at a rate of 5-10° C. / min, and the heat treatment is carried out at this temperature for 2-3 hours.
8. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 4, characterized in that: The flow ratio of argon to oxygen during plasma etching is 3-5:1, and the power during etching is set to 250-400W.
9. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 4, characterized in that: The frequency of ultrasonic dispersion in the second step is 25-35 kHz, and the ultrasonic dispersion time is 20-30 min.
10. The method for producing magnesia-carbon bricks by using low-carbon reduced magnesia according to claim 4, characterized in that: In the second step, high-temperature sintering is performed in a nitrogen atmosphere, and the temperature of the high-temperature sintering is 450-550° C., and the time of the high-temperature sintering is 2-3 hours.
Citation Information
Patent Citations
Magnesia carbon brick taking composite magnesia as major raw material and preparation method thereof
CN102093065A
Magnesia carbon bricks added with boron carbide, and preparation method of magnesia carbon bricks
CN107954697A
Metal-compounded low-carbon magnesia carbon brick for ladle slag line and preparation method thereof
CN110143807A
Low-E hollow glass and preparation method thereof
CN114057405A
Cited By
Magnesia-carbon refractory material containing metal-carbon complex phase and preparation method thereof
CN121990815A